2019
DOI: 10.1016/j.gca.2019.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Decimeter-scale mapping of carbonate-controlled trace element distribution in Neoarchean cuspate stromatolites

Abstract: Ancient stromatolites can provide key insights into the early evolution of life on Earth. Neoarchean fenestrate stromatolites from the ~2520 Ma Upper Nauga Formation (Transvaal Supergroup, South Africa) preserve cuspate morphologies. They possess clearly delineated support and drape structures interpreted as dolomitized microbial mat material. Petrographic observations show that the biogenic structures are composed of planar-s to non-planar ferroan dolomite, encased in ferroan calcite, including herringbone ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 117 publications
3
4
0
Order By: Relevance
“…The features are similar to those observed from stromatolites (see Warke et al, 2019) which form under conditions of generally deeper, and longer-lived, standing water than features observed within MF1. The features are similar to those observed from stromatolites (see Warke et al, 2019) which form under conditions of generally deeper, and longer-lived, standing water than features observed within MF1.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…The features are similar to those observed from stromatolites (see Warke et al, 2019) which form under conditions of generally deeper, and longer-lived, standing water than features observed within MF1. The features are similar to those observed from stromatolites (see Warke et al, 2019) which form under conditions of generally deeper, and longer-lived, standing water than features observed within MF1.…”
supporting
confidence: 77%
“…The presence of clotted and laminar microbial growth also indicate an environment that was wetter than that for MF1. The features are similar to those observed from stromatolites (see Warke et al, 2019) which form under conditions of generally deeper, and longer-lived, standing water than features observed within MF1.…”
supporting
confidence: 77%
“…Fabric destructive dolomitsation, driven by interaction of precursor carbonate phases with a burial brine, is also known to affect the Campbellrand Subgroup (Sumner, 1996). Dolomite precipitating from such a fluid could enrich Cu host dolostones up to concentrations of 150 -1500 ppm (Warke et al, 2019). As we do not observe concentrations above 126 ppm in this study, and this portion of GKF01 retains discernible microbial fabrics (Schröder et al, 2006; Therefore, there is no evidence -either from considering the sulphides themselves or from considering the susceptible host sediments -to suggest that Cu-sulphides have been significantly altered.…”
Section: Diagenesis and Metamorphismmentioning
confidence: 47%
“…Synchrotron X-Ray Fluorescence has shown that microbial fabric-retentive ferroan dolomite in GKF01 can contain up to 20 ppm Cu, although generally concentrations in the ferroan dolomite are lower than detection (~1 ppm; Warke et al, 2019). This form of dolomitisation, driven by seawater derived fluids (Warke et al, 2019), is common in the studied interval and is therefore unlikely to account for the higher Cu concentrations measured in this study.…”
Section: Diagenesis and Metamorphismmentioning
confidence: 59%
See 1 more Smart Citation